Endometrial and Cervical Malignancies in the Postmenopausal Population: Clinicopathologic Correlation and Survival Outcomes - Pulatova, Yulduz; Spogmai, Spogmai; Tariq , Beenish; Zafar, Faryal; Shams, Amber; Shams, Amber (Journal of Neonatal Surgery, 2024)
Background:Endometrial and cervical cancers collectively represent a substantial proportion of gynecologic malignancies worldwide, with a disproportionately high burden among postmenopausal women. Aging-related hormonal changes, metabolic disorders, and delayed symptom recognition contribute to late-stage diagnosis and variability in prognosis. While endometrial cancer is typically associated with unopposed estrogen exposure and metabolic syndrome, cervical cancer remains strongly linked to persistent high-risk HPV infection, inadequate screening coverage, and socioeconomic disparities. These cancers differ markedly in their biology, stage distribution, treatment responsiveness, and survival outcomes; however, literature specifically focusing on postmenopausal women remains limited despite their distinct risk profile and therapeutic challenges. Understanding these malignancies within this demographic is crucial for tailoring early detection strategies, improving prognostic modeling, and optimizing treatment. Objective:This review aims to integrate contemporary evidence on clinicopathologic features, histologic heterogeneity, prognostic markers, and survival outcomes of endometrial and cervical cancers in postmenopausal women, while comparing their biological behavior, stage patterns, treatment modalities, and determinants of survival. Methods:A systematic review of studies published between 2015 and 2024 was performed using major scientific databases (PubMed, Scopus, Web of Science). Eligible studies included observational, cohort, and registry-based analyses that reported demographic data, tumor characteristics, staging, treatment, and survival outcomes specific to postmenopausal patients. Data were extracted independently by two reviewers, summarized narratively, and pooled using random-effects meta-analysis where applicable. Study quality was assessed using the Newcastle–Ottawa Scale. Results:Twenty-eight studies encompassing 19,874 postmenopausal women were included. For endometrial cancer, early-stage diagnosis predominated and overall survival remained relatively favorable, though significantly diminished in aggressive histologic subtypes such as serous carcinoma and carcinosarcoma. In contrast, cervical cancer in postmenopausal women was frequently diagnosed at advanced stages, with suboptimal survival due to delayed presentation and reduced treatment accessibility. Shared determinants of survival included age, tumor stage, lymphovascular space invasion, lymph node status, and timely initiation of therapy. Despite advances in diagnostics and therapeutics, considerable heterogeneity exists in reporting outcomes specific to postmenopausal women. Conclusion:Endometrial and cervical cancers among postmenopausal women exhibit unique epidemiologic and biologic traits, yet their prognostic trajectories converge around stage, grade, and comorbidities. Targeted screening, molecular risk stratification, improved access to treatment, and standardized menopausal-specific reporting are essential to improving survival. Strengthening global prevention programs—such as HPV vaccination and metabolic risk reduction—can significantly reduce disease burden.